Isolated Orbital Metastasis from Breast Carcinoma: A Case Report - Sahni, Manish; Mehta, Harsha N; Gothwal, Ravindra; Lakhera, Kamal Kishor; Singh, Suresh (Asian Pacific Journal of Cancer Care, 2024)
Breast cancer with isolated orbital metastasis is a rare clinical entity. This report presents a case of a 35-year-old premenopausal woman with a known history of right-sided breast carcinoma. She underwent a right modified radical mastectomy in 2017, with final histopathology revealing pT2N2M0, hormone receptor-positive, and Her2-negative disease. She received adjuvant chemotherapy (8 cycles of standard dose) consisting of 4 cycles of cyclophosphamide and Adriamycin followed by 4 cycles of paclitaxel, and subsequent local radiation therapy. She was then initiated on tamoxifen 20 mg once daily for 4 years. In July 2021, she presented with a one-month history of sudden decreased visual acuity and diplopia in her right eye. Ophthalmological examination confirmed these findings, with decreased visual acuity of 6/36 in the right eye, while the left eye remained normal. A computed tomography (CT) scan of the orbits revealed a 28 × 18 mm heterogeneous enhancing soft tissue mass in the right orbital compartment, extrabulbar, occupying the postero-superior quadrant and inseparable from the lateral rectus muscle with optic nerve effacement. A positron emission tomography-computed tomography (PET-CT) scan did not detect any other metastatic lesions. She underwent surgical oophorectomy followed by a switch to aromatase inhibitor therapy. The patient achieved a complete response to treatment and has remained disease-free for the past two years.